Model Pemuridan Paulus kepada Titus serta Implikasinya bagi Pemberdayaan Jemaat dalam Pelayanan Gereja - Kurniawan, Ernest; Antonius, Yosef; Timadius, Hendrik (STTI Harvest Semarang, 2025)
Discipleship is a critical element in shaping spiritual character and leadership within the church. However, implementing effective discipleship models remains a challenge in many local churches. The Apostle Paul, through his mentoring relationship with Titus, presents a comprehensive and contextual example of discipleship. This study employs a qualitative method using a systematic literature review approach. Data sources include the Bible, classical and contemporary theological works, and relevant academic articles. Thematic analysis is applied to identify key elements in Paul’s discipleship model as reflected in his epistle to Titus. The findings show that Paul’s discipleship model incorporates personal relationships, sound doctrinal teaching, practical ministry equipping, exemplary living, training to face challenges, and the principle of multiplication. This process not only develops disciples but also produces leaders who can sustain and expand the ministry. Paul’s discipleship model with Titus serves as an ideal framework for modern churches seeking to empower their congregations. Discipleship is not merely a transfer of knowledge but a transformative process that nurtures faith and equips believers for active and responsible ministry involvement. AbstrakPemuridan merupakan elemen penting dalam pembentukan karakter rohani dan kepemimpinan dalam gereja. Namun, penerapan model pemuridan yang efektif masih menjadi tantangan di banyak gereja lokal. Paulus, melalui relasinya dengan Titus, memberikan teladan pemuridan yang menyeluruh dan kontekstual. Penelitian ini menggunakan metode sistematic literature review, pendekatan studi pustaka. Sumber data meliputi Alkitab, literatur teologis klasik dan kontemporer, serta artikel akademik yang relevan. Analisis dilakukan secara tematik terhadap elemen-elemen pemuridan Paulus yang dituliskan dalam suratnya kepada Titus. Ditemukan bahwa model pemuridan Paulus mencakup aspek relasi personal, pengajaran yang sehat, pembekalan untuk pelayanan, keteladanan hidup, pelatihan menghadapi tantangan, dan prinsip multiplikasi. Proses pemuridan tidak hanya membentuk murid, tetapi juga menghasilkan pemimpin yang mampu melanjutkan pelayanan. Model pemuridan Paulus kepada Titus menjadi pola ideal yang dapat diadaptasi gereja masa kini untuk memberdayakan jemaat secara efektif. Pemuridan tidak hanya menumbuhkan iman, tetapi juga memperlengkapi jemaat untuk terlibat aktif dan bertanggung jawab dalam pelayanan.